The Impact of E-Procurement on the Performance of Public Institutions in Rwanda (Global Journal of Management and Business Research, 2018)
The general objective of this study was to assess the impact of electronic procurement on the performance of public institutions in Rwanda. This study was mainly carried out following the reports that emerged citing poor performance of Rwandan public institutions which was mostly been attributed to ineffective and inappropriate running of the public finance during procurement processes. In order to reach the achievement of the research objectives, a combination of questionnaires, interviews, documentary reviews and analyzing reports were used to gather both primary and secondary data respectively from 42 respondents. Findings revealed that e-bidding offers a more efficient communication infrastructure with lower transaction costs. This was followed by the finding that MINECOFIN has experienced an improvement in the efficiency of procurement indicated by the application of electronic procurement. Hence, e-procurement has improved the performance of the ministry since it reduced its expenses from 24.4 million in 2015 to 18.6 million in 2016. Lastly, from the Chi-square test, the researcher learnt that e-procurement in terms of electronic bidding, electronic supplier registration, electronic billing and electronic payment is significantly related to the performance in MINEFCOFIN. Regarding functionality analysis by the top management should be looked into and made a culture by the responsible personnel at the ministry. The ministry was recommended to sensitize the general public on e-procurement system called “UMUCYO”. Strong relationship between the study’s variables was revealed after the chi-square test which was done out of the data gotten from the respondents. From the findings P-value (0.019) is less than the significance level (0.05), we then conclude that there is a correlation between e-procurement and performance at MINECOFIN.
Keywords: e-procurement; e-bidding; performance